Active Learning in Advanced Undergraduate Course of Thermodynamic and Statistical Physics - Zdeňka Koupilová; Petr Kácovský (Karolinum Press, 2017)
In the field of physics education, the last two decades are connected with a shift from teacher-centred traditional approach to student-centred active learning approaches. This contribution describes such a shift in an obligatory undergraduate course of advanced Thermodynamics and Statistical Physics for future physics teachers. Our goals were to verify applicability of active learning methods in the conditions of our faculty, to improve students' habits of regular work during the term and to inspire them as future teachers. The redesigned course was inspired mainly by the Peer Instruction method, enriched by Just-in-Time Teaching technique. While majority of published studies describes these methods when being used in large courses, in this case the whole study group included up to ten students. All the components of the course were designed according to the active learning approach, i.e. not only the instruction itself, but also targeted work with students' motivation, students' preparation for lessons, homework projects and assessment. Up to now, the redesigned course was run three times. Despite increased time demands placed both on students and lecturers, we consider our realization of the course successful - all students were active during lessons, worked on their current level and enhanced their attitudes towards learning. They appreciated the effort to get a deep conceptual insight into the problematics as well as broad variety in instruction and collaborative spirit of lessons.